High voltage power lines magnetic field system of active shielding with compensation coil different spatial arrangement - Kuznetsov, B.I.; Nikitina, T.B.; Bovdui, I.V. (Електротехніка і електромеханіка, 2019)
Aim. The synthesis of single-circuit system of active shielding of magnetic field, generated by group of high voltage power lines, with different spatial arrangement of shielding coil. Results. Three variant of single-circuit robust system of active shielding with different spatial arrangement of shielding coil synthesis results for reduction of a magnetic field generated by group of high voltage power lines is given. Цель. Синтез одноконтурной робастной системы активного экранирования магнитного поля, создаваемого группой высоковольтных линий электропередачи, с различным пространственным расположением экранирующей обмотки. Результаты. Приводятся результаты трех вариантов синтеза одноконтурной робастной системы активного экранирования с различным пространственным расположением экранирующей обмотки для уменьшения магнитного поля, создаваемого группой высоковольтных линий электропередачи.